THE EFFECT OF MASSAGE TECHNIQUES AND WARM COMPRESSES ON PERINEAL TRAUMA: A SCOPING REVIEW - Sukmawati Sukmawati; Furkon Nurhakim (Journal of Maternity Care and Reproductive Health, 2026)
Perineal trauma is commonly associated with vaginal delivery and can have adverse effects on maternal health and quality of life. One of the approaches to reducing perineal trauma is the use of massage therapy and warm compresses. The aim of this study is to obtain information regarding the effects of massage therapy and warm compresses on perineal trauma. This study employed a scoping review method to map the characteristics, types of interventions, and available scientific evidence regarding perineal massage and warm compresses. A literature search was conducted across six databases: PubMed, EBSCOhost, Scopus, Cambridge, Garuda, and SINTA, using the following keywords: woman in labor, perineal massage, hot compress, and perineal injury. The inclusion criteria were articles published between 2015 and 2025, written in Indonesian or English, available in full text, using RCT, clinical trial, or experimental study designs, and categorized as primary research. The outcomes of interest were perineal massage and warm compress interventions aimed at reducing perineal trauma. The exclusion criteria were articles published in predatory journals and literature reviews. The analysis included six articles discussing massage techniques and warm compresses for reducing perineal trauma. Four articles reported that perineal massage and warm compress interventions could reduce perineal trauma, whereas two articles found no significant difference between perineal massage and warm compresses in reducing perineal trauma.  Perineal massage and warm compress interventions can be recommended as non-pharmacological approaches to reduce perineal trauma during childbirth. Keywords: Perineal massage; perineal trauma; warm compress.